JIRA development cookbook : develop and customize plugins, program workflows, work on custom fields, master JQL functions, and more-- to effectively customize, manage, and extend JIRA /: develop and customize plugins, program workflows, work on custom fields, master JQL functions, and more-- to effectively customize, manage, and extend JIRA. (2011) - Unknown
No abstract available